2015
DOI: 10.1111/febs.13313
|View full text |Cite
|
Sign up to set email alerts
|

Chemical probing suggests redox‐regulation of the carbonic anhydrase activity of mycobacterial Rv1284

Abstract: The mycobacterial enzyme Rv1284 is a member of the b-carbonic anhydrase family that is considered essential for survival of the pathogen. The active site cavity of this dimeric protein is characterized by an exceptionally small volume and harbours a catalytic zinc ion coordinated by two cysteine and one histidine residue side chains. Using the natural products polycarpine and emodin as chemical probes in crystallographic experiments and stopped-flow enzyme assays, we report that the catalytic activity can be r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Cys-159, in the proximity of the HXK1 sugar-binding site, was found oxidized in both Col-0 and top1top2. In top1top2, BCA1/ SABP3, required for photosynthesis and CO 2 signaling and known to be inactivated by oxidation or S-nitrosylation of Cys-280 (Wang et al, 2009;Nienaber et al, 2015), was found underoxidized relative to Col-0. Several enzymes with roles in chloroplast biogenesis and photosynthetic pigment synthesis were differentially oxidized in top1top2.…”
Section: Discussion a Mass Spectrometry Label-free Approach To Characmentioning
confidence: 99%
“…Cys-159, in the proximity of the HXK1 sugar-binding site, was found oxidized in both Col-0 and top1top2. In top1top2, BCA1/ SABP3, required for photosynthesis and CO 2 signaling and known to be inactivated by oxidation or S-nitrosylation of Cys-280 (Wang et al, 2009;Nienaber et al, 2015), was found underoxidized relative to Col-0. Several enzymes with roles in chloroplast biogenesis and photosynthetic pigment synthesis were differentially oxidized in top1top2.…”
Section: Discussion a Mass Spectrometry Label-free Approach To Characmentioning
confidence: 99%
“…However, redox regulation of β-CA also occurs in non-photosynthetic organisms. For example, oxidation of the β-CA from the pathogen Mycobacterium tuberculosis can trigger the formation of a disulfide bond at the active site involving the cysteine residues that coordinate the catalytic metal ion, thereby leading to its inactivation [117]. In this case, oxidation can be triggered either by air and H 2 O 2 but also by some oxidative compounds derived from the host.…”
Section: Regulation Of Ca Expressionmentioning
confidence: 99%
“…Conserved hypothetical (b class carbonic anhydrase) 86 Carbon fixation, pH regulation-may counter oxidative stress and acidification during innate immune response Rv1332…”
Section: Rv0099 Fadd10mentioning
confidence: 99%